CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), DAN NET INTEREST MARGIN (NIM) TERHADAP PROFITABILITAS PADA BANK BUMN DI INDONESIA - Mardayanti, Selvia; Fatonah, Siti; Triana, Leni (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Profitability as measured by Return On Asset (ROA) at State-Owned Banks in Indonesia for the period 2016-2023. The research method used is the causality associative method with a quantitative approach and uses secondary data sourced from the financial statements of State-Owned Banks published by the Financial Services Authority (OJK). The research sample amounted to 32 data from 4 State-Owned Banks selected by saturated sampling method. The data analysis technique used is multiple linear regression test and hypothesis testing which is processed using IBM SPSS Statistics version 26. The results prove that partially Capital Adequacy Ratio (CAR) has no effect on Return On Asset (ROA), Loan to Deposit Ratio (LDR) has no effect on Return On Asset (ROA), and Net Interest Margin (NIM) has a significant effect on Return On Asset (ROA). While simultaneously Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) have a significant effect on Return On Asset (ROA) at State-Owned Banks in Indonesia for the period 2016-2023